Karakteristik Kasus Penyakit Pulpa pada Pasien Perawatan Endodontik Dengan Pembiayaan BPJS di RSUD Tarakan Jakarta - Dhinintya Hyta; Sri Darmayanti; Istiqamah Yusuf (CV. KAMPUS AKADEMIK PUBLISHING, 2026)
Pulp disease represents an advanced complication of dental caries that may lead to permanent tooth loss and impaired oral health-related quality of life. In the era of Indonesia’s National Health Insurance administered by BPJS Kesehatan, many patients present at advanced stages and frequently exhibit degenerative comorbidities that may aggravate pulpal conditions. This study aimed to analyze the characteristics of pulp disease cases among insured patients receiving endodontic treatment at RSUD Tarakan Jakarta from September to December 2025. A retrospective descriptive design was conducted using secondary medical record data with ICD-10 code K04 diagnoses. Of 235 visits, 115 cases (48.94%) involved pulp disease. Female patients predominated (63.48%) with a mean age of 42.12 years, mainly within the middle-adulthood group. Pulp necrosis (77.4%) was the most frequent diagnosis, indicating late-stage presentation. Comorbidities were identified in 70.6% of patients, primarily hypertension and diabetes mellitus. Root canal treatment was the main therapeutic approach compared with extraction. These findings highlight the substantial burden of pulp disease among insured patients and underscore the importance of early caries detection, strengthened preventive strategies, and multidisciplinary management for patients with systemic conditions.